187k views
0 votes
Solve the system of equations by substitution and enter your solution

y= x2 - 2x - 6
y= 4x + 10

Solve the system of equations by substitution and enter your solution y= x2 - 2x - 6 y-example-1

2 Answers

6 votes

Answer: (-2,2),(8,42)

Explanation:

Took the quiz

User Reinmar
by
4.8k points
2 votes

Answer:

The solutions are (-2, -8) and (8, 42).

Explanation:

The given equations

y= x^2 - 2x - 6

y= 4x + 10

both give y as a function of x. Thus, we can set them equal, which temporarily eliminates y as a variable.

Then: x^2 - 2x - 6 = 4x + 10

Group like terms on the left: x^2 - 6x - 16 = 0

Solve by factoring: x^2 - 6x - 16 = 0 = (x - 8)(x + 2) = 0. Then x = {-2, 8}.

Using y = 4x + 10, we find the corresponding y values one by one:

y = 4(-2) + 10 = -8 and y = 4(8) + 10 = 42.

The solutions are (-2, -8) and (8, 42).

User Carl Crott
by
4.6k points